Qualidade física, fisiológica e sanitária de sementes de Schinus terebinthifolius Raddi de diferentes plantas matrizes - Santos Neta, Maria das Mercês Serafim (2017)
Native to Brazil, Schinus terebinthifolius Raddi is a species known for the reddish-pink color of its fruits, which have great industrial economy importance, are sold as a condiment and also used for the recovery of degraded areas. This species can be sexually propagated, where studies regarding the seed quality to know its agronomic behavior are necessary. The present work was developed in the Laboratórios de Análise de Sementes and Fitopatologia of the Centro de Ciencias Agrárias of the Universidade Federal da Paraíba (CCA / UFPB), in Areia - PB, and aimed to evaluate the physical, physiological and sanitary quality of seeds of S. terebinthifolius, from 15 different mother plants located in Pocinhos - PB. Water content, color, one thousand seed weight, germination, vigor (first count, germination speed index (IVG), emergence, emergence speed index (IVE), length, root and shoot dry weight, in addition to a sanity test were evaluated. A completely randomized experimental design was used. The seeds of the mother plants used had low physiological potential and ranged from 2 to 36% among the plants in the same area considered as unsuitable for replanting due to the low vigor of the ir seeds. Potentially pathogenic fungi, characterized as field pathogens (Alternaria sp., Botrytis sp., Chaetomium sp., Cladosporium sp., Colletotrichum sp., Curvularia sp., Nigrospora sp., Pestalotia sp., Phitomices sp. and Phoma sp.) and storage (Aspergillus sp., A.niger, A. flavus, Fusarium sp., Penicillium sp. and Rhizopus sp.) were detected in the seed samples.